CHARACTERISTICS OF ISLAMIC TEACHINGS: Islamic Perspective of Universal Religion - Khoirul Amin; Sudarmadi Putra; Widi Aimi (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2023)
The concept of Islamic Universal is a concept that makes Islam a multi-dimensional religion, so that it negates discrimination of religion, The research methodology in this paper uses short qualitative powerwith typelibrary  research. The data source is text-scientific textanalyzed usingcontent analisys. research results explain that All understanding of Islamic teachings values can only be achieved if the Islamic teachings concepts and characteristics are developed through a humanistic understanding that refers to its universal nature. That is why, the characteristics of Islamic teachings can be analyzed using various approaches, both normatively, psychologically, historically, philosophically, sociologically, politically, economically and various other disciplines, it also includes some fields, as like religion, humanity which discusses about education, science, culture, social, economics, politics, life, social, health, work, issues, and Islam as a scientific discipline. Muslims must be able to accommodate important things of human value in several fields of knowledge based on the Islamic teachings universalism.